The Effect of Line and Age on The Egg External Characteristics of Japanese Quail - Luay Alsalihi; Ahmed Shaker; Questan Ameen; Myriam Ortega Torres (Basrah Journal of Veterinary Research)
External egg traits like egg length, breadth, shape index, volume and surface area play important roles for egg hatching, embryo growth, and chick survival. 313 fertilized eggs were collected from three genetic lines of Japanese quail named (white, brown, and gray) in four collected ages (57, 64, 71, and 78) days. After collecting the traits were measured by using electronic balance (0.001gm.) sensitivity, and caliper vernier (0.01 mm.). The data show significant differences between some traits and some of them differ with the age of birds and the interaction between the genetic lines and age of collecting eggs. Our results conclude there were significant differences between the three genetic lines on egg external traits and between the collecting age and their infarctions. May its helpful for future studies to establish lines special for egg production, or to make studies on molecular levels.